Sexual transmission of HCV between spouses - (:unkn) unknown (NATURE PUBLISHING GROUP, 2005)
BACKGROUND AND AIMS: The sexual transmission of hepatitis C virus (HCV) is debated. By excluding other risk factors, the role of sexual intercourse in the transmission could be detected more accurately. We screened HCV prevalence and risk factors in the spouses of chronic hepatitis C (CHC) patients and followed the seroconversion rate of anti-HCV negative spouses. PATIENTS AND METHODS: Six hundred spouses of CHC patients were recruited. The spouses' HCV risk factors were questioned and the spouses were tested for anti-HCV. The 216 spouses who were anti-HCV negative were checked annually for anti-HCV. RESULTS: Anti-HCV was positive in 12 of 600 (2%) of the spouses. Of the 12 anti-HCV positive spouses, 11 were HCV-RNA positive. Of anti-HCV positive and negative spouse groups, mean age was 52.3 +/- 9.8 and 49.8 +/- 12.4 yr; duration of marriage was 1521 +/- 506.7 and 1532.4 +/- 670.2 wk (p > 0.05); and the total number of sexual intercourse events was 434 +/- 295 and 307 +/- 333 (p = 0.055), respectively. In our prospective study, none of the spouses developed anti-HCV seroconversion in mean 35.7 +/- 6.3 months and 257.9 +/- 72.2 sexual intercourse. CONCLUSIONS: Anti-HCV was found positive in 2% of the spouses. None of the seronegative spouses developed seroconversion in the 3-yr follow-up period. This is the first study that stresses the importance of the total number of sexual intercourse events in sexual transmission (p = 0.055). Our results of special monogamous group with very limited risk factors support the role of number of total sexual intercourse in HCV transmission. However, the seroprevalence rate of the spouses was still within the upper limit of our country population.
Keywords: HEPATITIS-C VIRUS; RISK-FACTORS; TRANSMITTED-DISEASES; HOMOSEXUAL-MEN; INFECTION; EXPOSURE; COUPLES; SEMEN